Natural experiments for orthopaedic trauma research: An introduction. Issue 2 (February 2023) - van de Wall, Bryan J.M.; Stadhouder, Agnita; Houwert, R. Marijn; Oner, F. Cumhur; Beeres, Frank J.P.; Groenwold, Rolf H.H.; ,
Abstract: Natural experiments are observational studies of medical treatments in which treatment allocation is determined by factors outside the control of the investigators, arguably resembling experimental randomisation. Natural experiments in the field of orthopaedic trauma research are scarce. However, they have great potential due to the process governing treatment allocation and the existence of opposing treatment strategies between hospitals or between regions as a result of local education, conviction, or cultural and socio-economic factors. Here, the possibilities and opportunities of natural experiments in the orthopaedic trauma field are discussed. Potential solutions are presented to improve the validity of natural experiments and how to assess the credibility of such studies. Above all, it is meant to spark a discussion about its role within the field of orthopaedic trauma research.